Monolithically Assembled 3D Soft Transformable Robot. (21st September 2022) - Hwang, Jae Hyuk; Shin, Jeehae; Han, Jiseok; Choi, Yong-Seok; Park, Sungmin; Kim, Yun Ho; Kim, Yong Seok; Kang, Hong Suk; Kim, Dong-Gyun; Lee, Jong-Chan
Abstract : Transformable Robot In article number 2200051, Hong Suk Kang, Dong‐Gyun Kim, Jong‐Chan Lee, and co‐workers present photo‐controllable liquid crystalline networks (pc‐LCNs) comprising static and dynamic covalent dual‐cross‐links. The tailored network architecture of pc‐LCNs enable UV‐controllable reversible assembly/disassembly and shape reconfiguration capabilities, while maintaining visible light‐responsive actuation behaviors, thus realizing a building‐block‐like, monolithically assembled 3D soft transformable robot capable of versatile locomotion.